2022
DOI: 10.1002/its2.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant biostimulants on seedling root and shoot growth of three cool‐season turfgrass species in a controlled environment

Abstract: A plant biostimulant is a natural substance or microorganism applied to plants or soil to enhance growth and stress tolerance. The objective of this study was to measure the effect of six commercial plant biostimulants on root and shoot production in seedlings of three cool-season turf species grown in a controlled environment. Lolium perenne L., Agrostis palustris Huds., and Schedonorus arundinaceus Schreb. were seeded into tobacco float trays and, after germination, were installed in a hydroponic system rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Krasa and Świerszcz [123] noted in another study that a biostimulant containing HA enhanced the vitality of a turfgrass mixture composed of perennial ryegrass and Kentucky bluegrass. Similar observations were made by Acuña et al [130], who demonstrated that HA and complex organic materials exerted a positive effect on the performance of turfgrasses and identified differences in responses to the applied biostimulant between perennial ryegrass, creeping bentgrass and tall fescue. In the work of Erwin [131], HA significantly increased the mass and resistance of Kentucky bluegrass roots.…”
Section: Biostimulant Plant Species Effect Referencessupporting
confidence: 86%
See 1 more Smart Citation
“…Krasa and Świerszcz [123] noted in another study that a biostimulant containing HA enhanced the vitality of a turfgrass mixture composed of perennial ryegrass and Kentucky bluegrass. Similar observations were made by Acuña et al [130], who demonstrated that HA and complex organic materials exerted a positive effect on the performance of turfgrasses and identified differences in responses to the applied biostimulant between perennial ryegrass, creeping bentgrass and tall fescue. In the work of Erwin [131], HA significantly increased the mass and resistance of Kentucky bluegrass roots.…”
Section: Biostimulant Plant Species Effect Referencessupporting
confidence: 86%
“…Humic and fulvic acids tall fescue positive effects observed on transplanted tall fescue, improved quality and heat resistance [124,125] Humic and fulvic acids creeping bentgrass improved root growth at both low and higher fertiliser levels, increased photosynthetic rates and root mass regrowth, improved tolerance to heat and moisture stress, enhanced turfgrass quality [126][127][128] Humic and fulvic acids perennial ryegrass increased uptake of nutrients, promotion of root growth, improved drought tolerance, particularly concerning iron content [36,123,129,130] Humic and fulvic acids Kentucky bluegrass increased root mass and resistance [131] Seaweed extracts Kentucky bluegrass and tall fescue no significant influence on NDVI in frequently mowed turfgrasses [132] Seaweed extracts creeping bentgrass improved visual quality, enhanced shoot and root growth, mitigated summer decline in creeping bentgrass growth [42] Seaweed extracts perennial ryegrass, Kentucky bluegrass decreased prevalence of fungal diseases, increased turf density [133] Protein hydrolysates and free amino acid perennial ryegrass, Kentucky bluegrass, tall fescue improved appearance, functionality, disease resistance, increased nutrient content (N, K, Mg, Na, Mn) [47] Protein hydrolysates and free amino acid creeping bentgrass stimulated N and K uptake, increased grass quality, more shoots, longer roots, increased shoot number, absorbed glutamate for GABA and proline production [134,135] Fungi perennial ryegrass.…”
Section: Biostimulant Plant Species Effect Referencesmentioning
confidence: 99%
“…Biostimulants and TE maintained up to 76% and 56% more chlorophyll content, respectively, in leaves compared to leaves in nontreated turf (Xu and Huang 2010). Additionally, many biostimulants can improve overall turfgrass vigor, rooting, and shoot growth (Acuña et al 2022; Xu and Huang 2010; Zhang and Ervin 2008).…”
Section: Introductionmentioning
confidence: 99%